Costs and benefits of running an international currency - Papaioannou, Elias; Porte, Richard; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : Office for Infrastructures and Logistics in Brussels, 2008)
This report discusses the cost and benefits of running an international currency. It starts by discussing the effect of the euro's internationalization on financial markets, and presents data on the impact of the single currency on private credit. It considers recent work on the effect of the euro on financial integration and the implications of the euro's rising internationalization on the liquidity premium. Then it turns to the vehicle currency role of the euro and presents some results using new data from the latest BIS Triennial Survey on the foreign exchange market. Concerning the direct benefits of running an international currency, the report first offers estimates on the likely gains from international seigniorage and discuss work on the effects of the internationalization of the euro on the terms of trade and invoicing patterns in international trade. The implications of the international role of the euro for portfolio returns and the so-called "exorbitant privilege" are analysed in detail. The effects of the single currency on exchange rate volatility are also considered. It summarizes recent research on the impact of the euro on global bond and equity and analyzes the potential implications of the euro's international status for central banks' reserve holdings. Finally, it turns to the effects of the euro on the stability of domestic money demand and the problems posed for monetary policy, and the implications for international financial stability.
Economic Papers.